2021
DOI: 10.3847/1538-4357/abf1ed
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Helium Absorptions with 3D Hydrodynamics and Self-consistent Photochemistry. II. WASP-107b, Stellar Wind, Radiation Pressure, and Shear Instability

Abstract: This paper presents simulations of the metastable helium (He * ) observations of WASP-107b, so far the highest signal-to-noise ratio detection that is confirmed by three different instruments. We employ full 3D hydrodynamics coupled with coevolving nonequilibrium thermochemistry and ray-tracing radiation, predicting mass-loss rates, temperature profiles, and synthetic He * line profiles and light curves from first principles. We find that a stellar wind stronger than solar is demanded by the observed heavily b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
5
25
1
Order By: Relevance
“…On the other hand, our data only cover half of the transit, which limits the sensitivity of our measurement. If planet b has an extended egress comparable to that of WASP-69 b (Nortmann et al 2018) and WASP-107 b (Wang & Dai 2021b, Spake et al 2021, our data might still be consistent with a strong excess absorption signal during the transit. In this case the the transit-timing offset would need to be even larger, but we cannot exclude this possibility with the current partial phase coverage.…”
Section: Nondetections For V1298 Tau B and Csupporting
confidence: 69%
See 2 more Smart Citations
“…On the other hand, our data only cover half of the transit, which limits the sensitivity of our measurement. If planet b has an extended egress comparable to that of WASP-69 b (Nortmann et al 2018) and WASP-107 b (Wang & Dai 2021b, Spake et al 2021, our data might still be consistent with a strong excess absorption signal during the transit. In this case the the transit-timing offset would need to be even larger, but we cannot exclude this possibility with the current partial phase coverage.…”
Section: Nondetections For V1298 Tau B and Csupporting
confidence: 69%
“…Additionally, there is a potential degeneracy between the model limb darkening and the outflow geometry. Even for modest outflows, deviations from spherical symmetry in the extended metastable helium distribution can change the morphology of the light curve (Wang & Dai 2021a, 2021b. Both of these factors may contribute to the "V-shaped" appearance of the light curves, especially for planet d.…”
Section: The Stellar Helium Linementioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamic simulations of escaping planetary atmospheres generally predict that the escaped material should form a comet-like tail, further shaped by the interaction with the stellar wind. For WASP-107b specifically, the modeling work of Wang & Dai (2021b) shows that the evidence of a planetary tail should be observable in the He 10830 Å spectra.…”
Section: A Posttransit Tailmentioning
confidence: 99%
“…Several studies, including Dai (2021b) andMcCann et al (2019), have found that shear instabilities due to interaction with a stellar wind can change the level of absorption observed in transit light curves of escaping atmospheres. The greatest variability is seen in the pre and posttransit absorption; however, they also report low levels of variability between second and third contact.…”
Section: Variability In the Planetary Windmentioning
confidence: 99%